2019
DOI: 10.1111/wvn.12395
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Expression of Persons with Dementia: An Integrative Review with Implications for Evidence‐Based Practice

Abstract: Background: The ability to express emotion typically is preserved longer than language and cognitive function in persons living with dementia. Emotional expression may be an important indicator of underlying individual needs and feelings and may therefore facilitate person-centered care.Aims: This review aimed to examine how emotional expression has been described, measured, and utilized in empirical studies. Methods:The design of this study was an integrative literature review.Results: Most of the articles us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 37 publications
(47 reference statements)
0
20
0
Order By: Relevance
“…We have options, and it is essential to make use of them not only when being the receiver of socially relevant information but also when being the sender. And, we should use and optimize those options which we can best play and which suit us best; this not only applies for times and situations where we cover parts of our face due to health or cultural reasons but extends to cases where the ability to express emotions is affected (e.g., due to neurological diseases, Jin et al, 2017;Lee et al, 2019): some people might have only a very limited repertoire of gestures and other body-oriented expression abilities but they might be good verbal communicators. Emphasizing alternative and additional communicative channels (see Aviezer et al, 2008), we can provide sufficient information to keep social interaction going in a different, yet, effective way.…”
Section: Discussionmentioning
confidence: 99%
“…We have options, and it is essential to make use of them not only when being the receiver of socially relevant information but also when being the sender. And, we should use and optimize those options which we can best play and which suit us best; this not only applies for times and situations where we cover parts of our face due to health or cultural reasons but extends to cases where the ability to express emotions is affected (e.g., due to neurological diseases, Jin et al, 2017;Lee et al, 2019): some people might have only a very limited repertoire of gestures and other body-oriented expression abilities but they might be good verbal communicators. Emphasizing alternative and additional communicative channels (see Aviezer et al, 2008), we can provide sufficient information to keep social interaction going in a different, yet, effective way.…”
Section: Discussionmentioning
confidence: 99%
“…Of the instruments measuring emotions with acceptable content validity (OERS and MAX), OERS is the most frequently used ( Lee et al, 2019 ) instrument with the most extensively documented psychometric properties ( Lawton et al, 1996 , 1999 ). MAX (and FACS) requiring a close view of the face; problems with interpreting facial movement in persons wearing glasses, having facial hair, or facing more than 45 degrees away from the camera ( Cohn et al, 2007 ) reduces the clinical utility of these instruments in people living with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Former reviews have reported on a variety of observational measures for people living with dementia ( Curyto et al, 2008 ), including observational instruments specific for well-being and QoL in dementia ( Algar et al, 2016 ), and measurements of emotional expressions in dementia ( Lee et al, 2019 ). However, there is a lack of systematic reviews evaluating measurement instruments assessing momentary well-being in dementia that includes an evaluation against quality criteria and risk of bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They retain the emotional trace of film clips despite forgetting their narrative content, show preserved mutual gaze with their spouses, and have a heightened tendency to take on the emotions of those around them,” which, when negative, can manifest as BPSD ( Fredericks et al, 2018 , p. 471). As verbal communication abilities worsen in persons living with AD, emotions remain a key element of communication, and are preserved even into the late stages of the disease ( Lee et al, 2019a ). Even in later stages, while persons with AD may not have the capacity to recall the source of their emotional experience, their self-reported daily emotion retained validity and reliability ( Zhang et al, 2015 ).…”
Section: Consciousness In Alzheimer’s Disease: Preserved Cognitions Emotions and Subjective Experiencementioning
confidence: 99%